Knowledge, Attitude and Practice Towards Road Traffic Regulations Among University Students, Malaysia - AA , Redhwan; AJ, Karim (IIUM Medical Journal Malaysia, 2010)
Introduction: Each year, more than 20 million people are injured and 1.17 million are killed due to road traffic accidents. Developing countries account for over 85% of the deaths, and close to 90% of the disability caused by road traffic crashes worldwide. The objectives of this study were to determine the knowledge, attitudes and practice and the factors influencing university students in Malaysia concerning road traffic accident. Materials and Methods: This study was conducted among the students of Management and Science University, Malaysia. The questionnaire was distributed randomly to the students of the Faculty of Health and Life Sciences. Data was analyzed using SPSS version 13, T-test and ANOVA. Results: The total number of 109 students with the mean age of 20.94±1.89 years participated in this study. Approximately 39 (35.7%) of the participant had been involved in one or more than one road traffic accident. About 93.6% of them were very strongly/strongly convinced of seat belts importance. Multivariate analysis using the multiple linear regression method showed that age and attitude were significantly associated with the exposure to the accident. Conclusion: The study participants had moderate knowledge about road traffic regulations and most of them mentioned that high speed, drivers’ lack of awareness about traffic regulation and laws, and drivers’ non-compliance with traffic rules and regulation were the most important cause of road traffic accidents. Almost all students were very strongly/strongly convinced of seatbelts importance. Age and attitude were significantly associated with the exposure to the accident.